Analisis Faktor – Faktor Yang Mempengaruhi Indeks Pembangunan Manusia Di Sumatera Barat - Ekawati Berutu; Ragel Yona Putri; M Sandy Maulana; Asnidar Asnidar; Ahmad Ridha (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
IPM is an important indicator for measuring success in efforts to build the quality of human life (society/population) in Indonesia, including in West Sumatra Province. The aim of this research is to analyze gross regional domestic product, economic growth rate, Gini index and poverty in West Sumatra Province 2013-2022. The analytical method used in this research is multiple linear regression analysis. The data used in this research is secondary data and is a form of time series data. Based on the results of multiple linear analysis, PDRB per capita partially has a positive and significant effect on IPM in West Sumatra Province, while the Growth Rate and Gini Index partially have a negative and insignificant effect on IPM in West Sumatra Province and Poverty partially has a positive and insignificant effect on PDRB West Sumatra. Simultaneously GRDP Per Capita, Economic Growth Rate, Poverty and Gini Index have a significant effect on IPM. So the fifth hypothesis states that simultaneously PDRB per capita, economic growth rate, poverty and Gini index have a significant effect on IPM